What do we learn about the "Anemia Module" of the French language Peritoneal Dialysis ? Interest and Results - Issad Belkacem; Mireille Griuncelli; Christian Verger; Guy Rostoker (RDPLF, 2019)
Background: Anemia is commonly observed in patients with chronic kidney disease (CKD) as soon as the glomerular filtration rate falls below than 30 ml/min. CKD patients frequently have iron deficiency. The use of both erythropoiesis-stimulating agents (ESA) and iron therapy is the backbone of anemia management in CKD. For this reason, an adequate iron supply is mandatory to achieve the optimal therapeutic benefit of erythropoiesis stimulating agents (ESAs). Many groups agree that anemia in peritoneal dialysis (PD) patients is less severe than in hemodialysis (HD) patients and that there are important differences in treatment practices for anemia between PD and HD patients. Methods: Analysis of the Anemia module of the French Language Peritoneal Dialysis Registry (RDPLF) register from the database set up in 2005 with a study of the period 2010-2017. Results: Data from 568 patients who participated in the Anemia module were analysed during the 2010-2017 follow-up period. Their median age were 71 years, 42% were female, median dialysis vintage was 13 months, 40,5% of patients had diabetes mellitus, 74% of patients were treated with ESA, 23% were on oral iron and only 11% have received intravenous iron. In terms of biological assessment, the average hemoglobin level was close to 12 g/dl and median CRP was close to 5 mg/l. For the iron balance, ferritin reached an average level of 270 µg/l in 2013 and stabilized in 2017 at 200 µg/l. The transferrin saturation coefficient always fluctuated between 23 % and 25 % from year 2010 to year 2017. Conclusion: The results of the Anemia module of RDPLF register appear to be in line with the target values of the ERA-EDTA latest European guideline on anemia (ERBP 2013) and show the low use of intravenous iron in PD (usually as second line therapy).